Zebrafish as a good vertebrate model for molecular imaging using fluorescent probes - Ko, Sung-Kyun; Chen, Xiaoqiang; Yoon, Juyoung; Shin, Injae (Chemical Society reviews, 2011)
Fluorescent probes have been used extensively to monitor biomolecules and biologically relevant species in vitro and in vivo. A new trend in this area that has been stimulated by the desire to obtain more detailed information about the biological effects of analytes is the change from live cell to whole animal fluorescent imaging. Zebrafish has received great attention for live vertebrate imaging due to several noticeable advantages. In this tutorial review, recent advances in live zebrafish imaging using fluorescent probes, such as fluorescent proteins, synthetic fluorescent dyes and quantum dots, are highlighted.